ARBUSCULAR MYCORRHIZAL FUNGI INCREASED EARLY GROWTH OF GAHARU WOOD OF Aquilaria malaccencsis and A. crasna UNDER GREENHOUSE CONDITIONS - Maman Turjaman; Erdy Santoso; Yana Sumarna (Indonesian Journal of Forestry Research, 2006)
Gaharu wood stand has an important source of profits to the forest community in South and Southeast Asia tropical forest countries, but Aquilaria species have reduced in number and turn out to be endangered due to overexploitation.   Today,   the planting stocks of   Aquilaria species are not sufficient to sustain the yield of gaharu wood and promote forest conservation.  The objective of this study was to determine   the effect of   five arbuscular mycorrhizal (AM) fungi: Entrophospora sp., Gigaspora decipiens, Glomus clarum, Glomus sp. ZEA, and Glomus sp. ACA, on the early growth of  Aquilaria malaccensis and A. crasna under greenhouse conditions. The seedlings of  Aquilaria spp. were inoculated with Entrophospora sp., Gi. decipiens, Glomus clarum, Glomus sp. ZEA, Glomus sp. ACA and uninoculated (control) under greenhouse conditions. Then, percentage AM colonization, plant growth, survival rate and nitrogen (N) and phosphorus (P) content and mycorrhizal dependence (MD) were measured. The percentage AM colonization of A. malaccensis and A. crasna ranged from 83 to 97% and from 63 to 78%, respectively. Colonization by five AM fungi increased plant height, diameter, and shoot and root dry weights. N and P content of  the seedlings were also increased by AM colonization. Survival rates were higher in the AM-colonized seedlings at 180 days after transplantation than those in the control seedlings. The MD of Aquilaria species was higher than 55 %. The results suggested that AM fungi can be inoculated`to Aquilaria species under nursery conditions to obtain vigorous seedlings, and the field experiment is underway to clarify the role of AM fungi under field conditions.